The Limitations of International Humanitarian Law (IHL) in Protecting Civilians in the Saudi Arabia–Yemen Cross-Border Conflict - Maulana, Muhamad Silva (Journal of Law, Politic and Humanities, 2025)
The cross-border armed conflict between Saudi Arabia and Yemen since 2015 has triggered the worst humanitarian crisis of this century, with hundreds of thousands of civilians being killed. International Humanitarian Law (IHL) normatively guarantees civilian protection through the principles of distinction, proportionality, military necessity, and humanity. However, the reality shows systematic violations in the form of airstrikes on civilian facilities, blockades resulting in mass starvation, and the indiscriminate use of weapons. This research uses a normative-critical method with a study of primary documents (the 1949 Geneva Conventions, Additional Protocols I & II, UN reports, the ICRC, Amnesty International, and Human Rights Watch) and a case study of the Saudi-Yemeni conflict. The analysis shows that the limitations of IHL are primarily due to the absence of effective enforcement mechanisms, the politicization of the UN Security Council, the asymmetry between state and non-state actors, and the ambiguity of the classification of international and non-international conflicts. In conclusion, although IHL norms are legally strong, their implementation remains weak due to subordination to political and military interests. Therefore, strengthening enforcement mechanisms, reforming international governance, and adapting norms to hybrid conflicts are necessary to strengthen civilian protection in modern armed conflicts.